A Simple Method for Determining an Optimal Number of Access Points in Distributed WLAN Networks - Staniec, K.; Kowal, M. (Elektronika ir Elektrotechnika, 2013)
In large wireless installations based on WLAN systems, mechanisms governing their operation other than just those related to the radio coverage may play a crucial role in the customer experienced quality of service (EoS). In particular, two factors have been identified as having a particular impact on the final efficiency of the distributed WLAN network. The first one is the IEEE 802.11x protocol overhead (assisted with the choice of the preamble length) which is largely dependent on the kind of WLAN standard used – ‘b/g’, ‘a’ or ‘n’. The other factor is the MAC protocol scheme, the CSMA/CA, developed for the IEEE 802.11x family, identical for all its sub-standards. A simple formula has been developed that accounts for both these aspects and provides an easy-to-implement method allowing deployment of the minimum number of access points as a function of the expected number of users, assuring a guaranteed effective throughput per user at optimal utilization of the total available capacity. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5658